Social Stratification In William Shakespeare's Cymbeline (1623): Marxist Perspective - Wahyuni, Sri (2012)
This study aims at analyzing Cymbeline drama based on the structural elements of drama and analyzing Cymbeline drama using Marxist perspective. The study uses qualitative method. The object of the study is Cymbeline drama written by William Shakespeare in 1623. The theoretical approach uses Marxist perspective. The technique of data collection is library research and the steps are as follows: determining the character that will be analyzed, taking note on important parts in both primary and secondary data, classifying and determining the relevant data, and taking notes from the material and some other resources related to the drama. The outcome of the study shows the following conclusions: (1) based on the structural analysis, it is clear that in this drama, the author wants to send the message to the reader that "Love does not care for social stratification" and (2)based on the Marxist perspective analysis, it is the evident that in this drama, the author reflects the social situation of the English society in early seventeenth century that emphasized the social stratification.